Catalyst, method and application
By using a metal nanoparticle catalyst encapsulated with all-silicon molecular sieve in the furanformaldehyde decarbonylation method, the problems of poor catalyst stability and low selectivity are solved, and the catalytic effect with high conversion and high selectivity is achieved.
Patent Information
- Application Number
- CN202311267387.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The metal Pd of the catalyst in the existing furan formaldehyde decarbonylation method is unevenly dispersed, resulting in poor catalyst stability and low selectivity.
A catalyst for encapsulating metal nanoparticles is used to use a fully silicon molecular sieve. The particle size of the metal nanoparticles is 0.5 to 3.5 nm, and is dispersed inside the whole silicon molecular sieve to form a sheet-like structure.
The conversion rate of furan formaldehyde and the selectivity of furan are improved. The conversion rate of furan formaldehyde can reach 100%, and the selectivity of furan can reach 96.2%, while improving the stability of the catalyst.
Smart Images

Figure CN119702047A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst, a method and an application, and in particular to a catalyst, a method and an application for decarbonylating furan formaldehyde to prepare furan. Background Art
[0002] Furan is a valuable chemical raw material that can be used to produce pharmaceutical intermediates such as α-acetylfuran, 2,2-difuran propane, and pyrrole derivatives. It is also widely used in the synthesis of polymers such as adhesives, vinyl films, and cellophane. There are several methods for synthesizing furan, among which furan carboxaldehyde decarbonylation is currently the method with the highest yield of furan. It can achieve the catalytic conversion of furan carboxaldehyde, a biomass-derived platform product, and establish a green industry chain for the preparation of furan through biomass routes, which plays an important role in responding to energy crises and environmental issues.
[0003] The method of furan decarbonylation to produce furan can be divided into liquid phase and gas phase decarbonylation. CN101822982A discloses a high-efficiency supported noble metal catalyst for furan decarbonylation to produce furan in liquid phase. The catalyst is γ-Al 2 O 3 -TiO 2 The composite oxide based on is used as the carrier, the palladium loading is 2-4wt% of the carrier, and K, Cs, Ru, Li, Rh, Na, La or Ba promoter is added to the catalyst, and its content is 0.5-2.0wt%. The furan formaldehyde liquid phase decarbonylation reaction is carried out under the conditions of pressure 0-0.5MPa and temperature 180-230℃, the furan formaldehyde conversion rate is 90-99%, the furan yield is 80-95%, and the catalyst life is 100-120h. The biggest disadvantage of the liquid phase decarbonylation method is that the high content of metal Pd is unevenly dispersed on the catalyst, the catalyst stability is too poor, and it is easy to deactivate.
[0004] CN1308986A discloses a highly efficient supported noble metal catalyst for producing furan by gas phase decarbonylation of furan formaldehyde. 2 O 3 -TiO 2 The composite oxide is used as the carrier, the platinum loading is 0.4-0.7wt% of the carrier, and K is added to the catalyst. 2 O、Cs 2 O, MgO, CaO or BaO and other promoters, the content of which is 0.5-2.0wt%. At normal pressure, 280°C, and furan formaldehyde space velocity of 0.9h -1 The reaction is carried out under the condition that the molar ratio of furan carboxaldehyde to hydrogen is 0.5-2.0, the furan carboxaldehyde conversion rate is 80-97%, and the furan selectivity is 85-92%.
[0005] CN111298818B discloses a highly efficient supported precious metal catalyst for producing furan by decarbonylation of furan formaldehyde in gas phase. The catalyst is represented by AC / B, wherein: AC is an active component; A is one of metal palladium and platinum; C is a carbonate of Li, Na, K, Mg, Ca, and La; the total loading amount of the active component AC in the catalyst is 1.05-60%, the loading amount of A is 0.05-10wt%, and the loading amount of C is 1-50wt%. B is a multi-level porous carrier with a nanosheet structure, which is one of nanosheet-type alumina and nanosheet-type molecular sieve. When reacting at normal pressure and 200-400°C, the furan yield is higher than 73%.
[0006] The conversion rate of furan formaldehyde and the selectivity of furan in the above literature still have room for further improvement. Summary of the invention
[0007] In view of this, one object of the present invention is to provide a catalyst, which contains all-silicon molecular sieve and metal nanoparticles, which can be used for catalytic decarbonylation of furan carboxaldehyde to obtain furan, and the conversion rate of furan carboxaldehyde and the selectivity of furan are high, the conversion rate of furan carboxaldehyde can reach 100%, and the selectivity of furan can reach 96.2%. Another object of the present invention is to provide a method for preparing the catalyst. Another object of the present invention is to provide the application of the catalyst. Another object of the present invention is to provide a method for preparing furan by decarbonylation of furan carboxaldehyde. The present invention achieves the above objects through the following technical solutions.
[0008] In one aspect, the present invention provides a catalyst comprising an all-silicon molecular sieve and metal nanoparticles; wherein:
[0009] The particle size of the metal nanoparticles is 0.5 to 3.5 nm; the metal nanoparticles are dispersed inside the all-silicon molecular sieve;
[0010] The metal element in the metal nanoparticles is selected from one or more of Pd, Pt and Rh; based on 100 parts by weight of the catalyst, the metal nanoparticles are 0.2 to 4.5 parts by weight; the catalyst has a flaky structure. Such a catalyst can be used in the catalytic decarbonylation of furan formaldehyde (i.e. furfural) to produce furan, which can improve the conversion rate of the raw materials and the selectivity of the target product.
[0011] The structural formula of furanaldehyde is shown in formula (1):
[0012]
[0013] The catalyst of the present invention is a catalyst formed by encapsulating metal nanoparticles in an all-silicon thin-sheet molecular sieve, and the metal nanoparticles are dispersed inside the molecular sieve and are basically evenly distributed inside the all-silicon molecular sieve. The aluminum oxide content of the all-silicon molecular sieve of the present invention is basically zero, and it can also be called Silicalite-1 molecular sieve.
[0014] The particle size of the metal nanoparticles is 0.5 to 3.5 nm, preferably 1 to 3 nm, for example, 0.5 nm, 1.0 nm, 1.5 nm, 2 nm, 2.5 nm or 3 nm.
[0015] Based on 100 parts by weight of the catalyst, the metal nanoparticles may be 0.2 to 4.5 parts by weight, preferably 0.2 to 3 parts by weight. For example, it may be 0.2, 0.3, 0.4, 0.5, 1.0, 2.0, 3.0, 4.0 or 4.5 parts by weight. Such a catalyst can both improve the conversion rate of the raw material and maintain a high selectivity of the target product.
[0016] The catalyst of the present invention is in the form of a sheet, and further, it has a flaky structure, and its crystal thickness is 15 to 30 nm, preferably 15 to 25 nm. For example, it can be 15 nm, 20 nm, 25 nm or 30 nm. The catalyst of the present invention has a hexagonal flaky structure, preferably, it is composed of hexagonal flakes with a thickness of about 20 nm, the crystal thickness is uniform, and there is a relatively large surface area, which is conducive to increasing the reaction site and reducing the diffusion restriction, so that it is used in the catalytic furan carboxaldehyde decarbonylation to furan reaction process, has excellent catalytic activity and structural stability, and in the process of catalyzing the furan carboxaldehyde decarbonylation to furan reaction, the conversion rate of furan carboxaldehyde can reach 100%, and it also has high selectivity for the product furan.
[0017] The catalyst of the present invention is formed by a water-soluble metal salt (i.e., a precursor of metal nanoparticles) and a silicon-containing raw material capable of forming an all-silicon molecular sieve; wherein the water-soluble metal salt is preferably a complex of a water-soluble metal salt and ethylenediamine. The silicon-containing raw material is selected from silicate or alkaline silica sol.
[0018] According to the catalyst of the present invention, preferably, the metal element in the metal nanoparticles is selected from one of Pd, Pt and Rh. This is beneficial to improve the conversion rate of raw materials and the selectivity of target products in the furan formaldehyde decarbonylation reaction to furan.
[0019] According to the catalyst of the present invention, preferably, the catalyst has a hexagonal sheet structure, which is conducive to reducing diffusion limitation.
[0020] On the other hand, the present invention also provides a method for preparing the catalyst as described above, comprising the following steps:
[0021] Step 1, mixing a silicon-containing raw material, alkylammonium hydroxide and water to obtain a first mixture; preliminarily crystallizing the obtained first mixture at 50-100° C. to obtain a seed suspension; the molar ratio of silicon element, alkylammonium hydroxide and water in the silicon-containing raw material is 1:0.1-0.5:6-26;
[0022] Step 2, mixing a silicon-containing raw material, alkylammonium hydroxide, alkylammonium bromide, a water-soluble metal salt and water to obtain a solution A; wherein in the solution A, the molar ratio of the silicon element in the silicon-containing raw material, the alkylammonium hydroxide, the alkylammonium bromide, the metal element in the water-soluble metal salt solution and water is 1:0.01-0.4:0.01-0.4:0.0004-0.03:20-200;
[0023] Step 3, mixing the seed suspension in step 1 and the solution A in step 2 to obtain a second mixture; wherein the molar ratio of silicon in the seed suspension to silicon in the solution A is 0.5 to 2.5:1;
[0024] Step 4, mixing the ammonium fluoride-containing solution B with the second mixture to obtain a third mixture; wherein the molar ratio of ammonium fluoride to water in the ammonium fluoride-containing solution B is 1:30-300; and the molar ratio of silicon element in the second mixture to ammonium fluoride in the solution B is 1:0.05-0.8;
[0025] Step 5, crystallizing the third mixture at 150-180° C., separating the solid and the liquid, and obtaining an initial solid; washing and drying the obtained initial solid to obtain a dry solid; and then reducing the dry solid in a hydrogen atmosphere at 350-450° C. to obtain the catalyst.
[0026] in,
[0027] In step 1, the molar ratio of silicon in the silicon-containing raw material to alkylammonium hydroxide is preferably 1:0.1-0.4, more preferably 1:0.2-0.4. The molar ratio of silicon in the silicon-containing raw material to water is preferably 1:5-25, more preferably 1:5-15, and further preferably 1:5-10, for example 1:10.
[0028] According to one embodiment of the present invention, the silicon-containing raw material, alkylammonium hydroxide and water are mixed and stirred at 20 to 45° C. for 6 to 12 hours to obtain a first mixture. The mixing temperature may be 20 to 45° C., preferably 20 to 40° C., such as 30° C. or 35° C. The stirring time may be 6 to 12 hours, preferably 8 to 10 hours.
[0029] In the present invention, the temperature of the initial crystallization can be 50-100° C., preferably 50-80° C., and more preferably 70-80° C. The time of the initial crystallization nucleation can be 24-96 hours, preferably 48-72 hours. The present invention finds that in the step of obtaining the seed suspension, the time and temperature range of the initial crystallization nucleation need to be controlled. If it is not within the scope of the present invention, it is not conducive to the formation of a flake catalyst for furan formaldehyde decarbonylation to furan.
[0030] In step 2, the mixing temperature can be 20 to 45°C, preferably 20 to 40°C, for example, 30°C or 35°C. In solution A, the molar ratio of silicon in the silicon-containing raw material to alkylammonium hydroxide can be 1:0.01 to 0.4, preferably 1:0.05 to 0.2. The molar ratio of silicon in the silicon-containing raw material to alkylammonium bromide can be 1:0.01 to 0.4, preferably 1:0.05 to 0.2. The molar ratio of silicon in the silicon-containing raw material to water can be 1:20 to 200, preferably 1:20 to 160, more preferably 1:30 to 110, for example 1:100. The molar ratio of the metal element in the water-soluble metal salt to the silicon in the silicon-containing raw material can be 0.0004 to 0.03:1, preferably 0.0004 to 0.025:1.
[0031] The silicon-containing raw material is selected from silicate or alkaline silica sol, preferably silicate. Silicate is selected from one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl orthosilicate, butyl orthosilicate, preferably ethyl orthosilicate. Alkyl ammonium hydroxide is selected from one or more of tetramethyl ammonium hydroxide, tetraethyl ammonium hydroxide, tetrapropyl ammonium hydroxide, dimethyl diethyl ammonium hydroxide, dimethyl dipropyl ammonium hydroxide, preferably tetrapropyl ammonium hydroxide. Alkyl ammonium bromide is selected from one or more of tetramethyl ammonium bromide, tetraethyl ammonium bromide, tetrapropyl ammonium bromide, preferably tetrapropyl ammonium bromide. The water-soluble metal salt is a complex of a water-soluble metal salt and ethylenediamine, such as a complex of a metal chloride and ethylenediamine. The metal element in the water-soluble metal salt is consistent with the metal element in the metal nanoparticles.
[0032] In step 3, the mixing temperature may be 20 to 45° C., preferably 20 to 40° C., for example 30° C. or 35° C. The mixing time may be 0.5 to 6 hours, preferably 4 to 6 hours. In the second mixture, the molar ratio of silicon in the seed suspension to silicon in solution A may be 0.5 to 2.5:1, preferably 0.5 to 1.5:1.
[0033] In step 4, solution B is an ammonium fluoride solution. In certain embodiments, the step of preparing solution B is further included, including: preparing ammonium fluoride and water into solution B, and stirring evenly; the molar ratio of ammonium fluoride to water is 1:30 to 300. In solution B, the molar ratio of ammonium fluoride to water is preferably 1:150 to 300.
[0034] In step 4, the mixing temperature may be 20 to 45° C., preferably 20 to 40° C., such as 30° C. or 35° C. The mixing time may be 0.5 to 3 h, preferably 1 to 3 h.
[0035] The molar ratio of silicon in the second mixture to ammonium fluoride in solution B is 1:0.05-0.8; preferably 1:0.2-0.6. The present invention finds that the addition of ammonium fluoride can make the flakes grow thinner and larger, which is more conducive to the catalytic performance of the catalyst. However, the amount of ammonium fluoride should not be too much, which will affect the metal encapsulation into the flake catalyst. The flake post-treatment process adopts a direct reduction method, and roasting will also affect the metal encapsulation into the flake molecular sieve catalyst.
[0036] In step 5, the crystallization temperature may be 150 to 180° C., preferably 170 to 180° C., for example 170° C. or 175° C. The stirring time may be 0.5 to 3 hours, preferably 1 to 3 hours. The solid-liquid separation may be centrifugation or suction filtration.
[0037] In the present invention, the washing is preferably carried out with water, preferably until the pH value of the washing solution is 7 (i.e., neutral). The drying temperature can be 100 to 120°C, preferably 105 to 110°C. The drying time can be 2 to 10 hours, preferably 8 to 10 hours. During reduction, the heating rate can be controlled to be 2 to 11°C / min, preferably 3 to 5°C / min. The temperature of reduction under a hydrogen atmosphere can be 350 to 450°C, preferably 380 to 420°C, for example, 400°C. The reduction time can be 1.5 to 4 hours, preferably 2 to 3 hours.
[0038] According to the preferred technical scheme of the present invention, the present invention adopts silicon-containing raw materials, tetrapropylammonium hydroxide, tetrapropylammonium bromide, ammonium fluoride, water and a water-soluble metal salt-ethylenediamine complex, and controls their dosage within a specific range, as well as controls the temperature and the preliminary crystallization and crystallization processes, so as to obtain the catalyst of the present invention with a specific morphology and thickness suitable for the decarbonylation of furan formaldehyde to furan.
[0039] According to the method of the present invention, preferably, the silicon-containing raw material is selected from silicate or alkaline silica sol; the silicate is selected from one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl orthosilicate and butyl orthosilicate.
[0040] According to the method of the present invention, preferably, the alkylammonium hydroxide is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, dimethyldiethylammonium hydroxide and dimethyldipropylammonium hydroxide.
[0041] According to the method of the present invention, preferably, the alkylammonium bromide is selected from one or more of tetramethylammonium bromide, tetraethylammonium bromide and tetrapropylammonium bromide.
[0042] According to the method of the present invention, preferably, the water-soluble metal salt is a complex of a water-soluble metal salt and ethylenediamine.
[0043] According to one embodiment of the present invention, the method for preparing the catalyst comprises the following steps:
[0044] Step 1, stirring and mixing a silicon-containing raw material, alkylammonium hydroxide and water at 20-45° C. for 6-12 hours to obtain a first mixture; preliminarily crystallizing the obtained first mixture at 50-100° C. for 24-96 hours to obtain a seed suspension; the molar ratio of silicon element, alkylammonium hydroxide and water in the silicon-containing raw material is 1:0.1-0.5:6-26;
[0045] Step 2, mixing a silicon-containing raw material, alkylammonium hydroxide, alkylammonium bromide, a water-soluble metal salt-ethylenediamine complex and water at 20-45° C. to obtain a solution A; wherein in the solution A, the molar ratio of the silicon element in the silicon-containing raw material, the alkylammonium hydroxide, the alkylammonium bromide, the metal element in the water-soluble metal salt-ethylenediamine complex and water is 1:0.01-0.4:0.01-0.4:0.0004-0.03:20-200;
[0046] Step 3, stirring and mixing the seed suspension in step 1 and the solution A in step 2 at 20-45° C. for 0.5-6 hours to obtain a second mixture; wherein the molar ratio of silicon in the seed suspension to silicon in the solution A is 0.5-2.5:1;
[0047] Step 4, stirring and mixing the solution B containing ammonium fluoride and the second mixture at 20-45° C. for 0.5-3 h to obtain a third mixture; wherein the molar ratio of ammonium fluoride to water in the solution B containing ammonium fluoride is 1:30-300; and the molar ratio of silicon element in the second mixture to ammonium fluoride in the solution B is 1:0.05-0.8;
[0048] Step 5, crystallizing the third mixture at 150-180° C. for 0.5-3 h, separating the solid and the liquid to obtain an initial solid; washing and drying the obtained initial solid to obtain a dry solid; and then reducing the dry solid in a hydrogen atmosphere at 350-450° C. for 1.5-4 h to obtain the catalyst.
[0049] In another aspect, the present invention also provides use of the catalyst as described above in catalytic decarbonylation of furan carboxaldehyde to prepare furan.
[0050] In another aspect, the present invention also provides a method for preparing furan by catalytic decarbonylation of furan carboxaldehyde, wherein the catalyst as described above is used to catalytically decarbonylate furan carboxaldehyde to prepare furan, and the weight ratio of the catalyst to furan carboxaldehyde is 1:1-20. The catalytic process conditions are: the reaction pressure is normal pressure, the molar ratio of hydrogen to furan carboxaldehyde is 50-150:1, the reaction temperature is 220-260°C, and the furan carboxaldehyde space velocity is 0.7-0.9h -1 The weight ratio of the catalyst to furfural is preferably 1:1-10.
[0051] The molar ratio of hydrogen to furfural is preferably 70 to 90:1, more preferably 75 to 85:1. The reaction temperature is preferably 245 to 250°C. The furfural space velocity is preferably 0.75 to 0.8 h -1 Such conditions are more conducive to the catalyst-catalyzed decarbonylation of furanaldehyde to furan.
[0052] The catalyst of the present invention can be used to catalyze the reaction of furan decarbonylation to furan, so that the selectivity of furan is higher and the conversion rate of the raw material furan is higher. The catalyst of the present invention is a sheet catalyst, which includes an all-silicon molecular sieve and metal nanoparticles, and the metal nanoparticles are dispersed inside the all-silicon molecular sieve. The method of the present invention can obtain a catalyst for furan decarbonylation to furan with a specific morphology and thickness. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 is the X-ray diffraction pattern of the catalyst prepared in Example 1 of the present invention;
[0054] Figure 2 is a SEM image of the catalyst prepared in Example 1 of the present invention;
[0055] Figure 3 is a TEM image of the catalyst prepared in Example 1 of the present invention;
[0056] Figure 4 is the X-ray diffraction pattern of the catalyst prepared in Examples 3 and 4 of the present invention;
[0057] Figure 5 is a SEM image of the catalyst prepared in Example 3 of the present invention;
[0058] Figure 6 is the X-ray diffraction pattern of the catalyst prepared in Example 5 of the present invention;
[0059] Figure 7 is the X-ray diffraction pattern of the catalysts prepared in Examples 6 and 7 of the present invention and Comparative Example 1;
[0060] Figure 8is a SEM image of the catalyst prepared in Comparative Example 1 of the present invention;
[0061] Fig. 9 This is the activity diagram of the furan formaldehyde decarbonylation to furan reaction of the catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0062] <Analysis Method>
[0063] The following describes the analysis method or analysis equipment used in the examples of the present invention:
[0064] X-ray diffraction pattern: Bruker D8 advance X-ray powder diffractometer was used.
[0065] SEM image: Regulus 8100 scanning electron microscope produced by Japan HITACHI Company was used; test conditions: after the sample was dried, vacuum evaporated to increase the conductivity and contrast effect, the acceleration voltage of the analysis electron microscope was 20.0kV, and the magnification was 30-110K.
[0066] TEM image: JEOL-JEM-2100F field emission transmission electron microscope was used; test conditions: the sample was dried and then evaporated in vacuum to increase the conductivity and contrast effect; the acceleration voltage of the analysis electron microscope was 20.0 kV, and the magnification was 1-20K.
[0067] Elemental analysis: The metal atom content in the molecular sieve was tested using an inductively coupled plasma atomic emission spectrometer (ICP-OES) from Varian, Germany. Before characterization, the sample was digested in an HF aqueous solution at room temperature.
[0068] Example 1
[0069] TEOS, tetrapropylammonium hydroxide and water were mixed and stirred at 35°C for 6 hours to obtain a first mixture; the first mixture was preliminarily crystallized at 70°C for 60 hours to obtain a seed suspension, wherein the molar ratio of silicon element in TEOS, tetrapropylammonium hydroxide and water was 1:0.4:10.
[0070] Ethyl orthosilicate, tetrapropylammonium hydroxide, tetrapropylammonium bromide, a complex of palladium chloride-ethylenediamine and water are uniformly mixed to obtain solution A. In solution A, the molar ratio of silicon element in ethyl orthosilicate, tetrapropylammonium hydroxide, tetrapropylammonium bromide, metal element palladium in the complex of palladium chloride-ethylenediamine and water is 1:0.1:0.1:0.0045:110.
[0071] The seed suspension and solution A were stirred and mixed for 4 hours to obtain a second mixture, wherein the molar ratio of silicon in the seed suspension to silicon in solution A was 0.8:1.
[0072] The ammonium fluoride solution (ie, solution B) and the second mixture were stirred and mixed for 1.5 hours to obtain a third mixture, wherein the molar ratio of ammonium fluoride to water in solution B was 1:150; and the molar ratio of silicon in the second mixture to ammonium fluoride in solution B was 1:0.4.
[0073] The third mixture was crystallized at 170°C for 72 hours and centrifuged to obtain an initial solid; the obtained initial solid was washed with water until neutral, and dried to obtain a dry solid; the dry solid was then placed in a reduction kettle, heated to 400°C at a heating rate of 3°C / min, and reduced at this temperature and in a hydrogen atmosphere for 2 hours to obtain a catalyst.
[0074] The obtained catalyst was analyzed and its X-ray diffraction pattern was shown in Figure 1 , SEM and TEM images are shown in Figure 2 and Figure 3 .Depend on Figure 1 It can be seen that the diffraction pattern shows that the catalyst is an all-silicon molecular sieve without any characteristic diffraction peak corresponding to the palladium element, indicating that no large Pd particles are formed in the synthesized sample. Figure 2 and Figure 3 It can be seen that the morphology of the catalyst obtained in this embodiment is uniform, basically hexagonal, and the average crystal thickness is 20nm. The surface of the catalyst is smooth, without obvious granular substances. According to elemental analysis, based on 100 parts by weight of the catalyst, the metal Pd element in the catalyst is 0.91 parts by weight, which is in line with the theoretical feed. The metal Pd nanoparticles are uniformly encapsulated by the all-silicon molecular sieve, and the particle size is 0.5 to 2.0nm.
[0075] Example 2
[0076] Except for the following parameters and settings, the rest are the same as those in Example 1: In solution A, the molar ratio of silicon element to palladium element is 1:0.0135.
[0077] The X-ray diffraction pattern of the catalyst obtained in this embodiment shows an all-silicon molecular sieve without any characteristic diffraction peak corresponding to the palladium element. The morphology of the obtained catalyst is uniform, basically hexagonal, and its crystal thickness is 25nm on average. The surface of the catalyst is smooth and there is no obvious granular material. According to elemental analysis, based on 100 parts by weight of the catalyst, the metal Pd element in the catalyst is 2.94 parts by weight, which is in line with the theoretical feed. The metal Pd nanoparticles are uniformly encapsulated with a particle size of 0.7 to 2.1nm.
[0078] Example 3
[0079] Except for the following parameters and settings, the rest are the same as Example 1: the palladium chloride-ethylenediamine complex is replaced by a rhodium chloride trihydrate-ethylenediamine complex.
[0080] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 4 As shown by Figure 4 It can be seen that the diffraction pattern shows that it is a full-silicon molecular sieve, without any characteristic diffraction peak corresponding to the rhodium element. Figure 5 ,Depend on Figure 5 It can be seen that the morphology of the catalyst obtained in this embodiment is uniform, basically hexagonal, and the average crystal thickness is 25nm. The surface of the catalyst is smooth, without obvious granular substances. According to elemental analysis, based on 100 parts by weight of the catalyst, the metal Rh element in the catalyst is 0.79 parts by weight, which is consistent with the theoretical feed. The metal Rh nanoparticles are uniformly encapsulated, and the particle size is 0.5 to 1.8nm.
[0081] Example 4
[0082] Except for the following parameters and settings, the rest are the same as Example 1: the palladium chloride-ethylenediamine complex is replaced by a chloroplatinic acid-ethylenediamine complex, and in solution A, the molar ratio of silicon element to platinum element is 1:0.00135.
[0083] The X-ray diffraction pattern of the catalyst prepared in this example (see Figure 4 ), the diffraction pattern shows an all-silicon molecular sieve without any characteristic diffraction peak corresponding to the platinum element. The morphology of the obtained catalyst is uniform, basically hexagonal, and its crystal thickness is 23nm on average. The surface of the catalyst is smooth, without obvious granular substances. According to elemental analysis, based on 100 parts by weight of the catalyst, the metal Pt element in the catalyst is 0.29 parts by weight, which is consistent with the theoretical feed. The metal Pt nanoparticles are uniformly encapsulated, with a particle size of 0.6 to 1.7nm.
[0084] Example 5
[0085] Except for the following parameters and settings, the rest are the same as Example 1: in solution A, the molar ratio of silicon element in tetraethyl orthosilicate to water is replaced by 1:30; and in solution B, the molar ratio of ammonium fluoride to water is 1:75.
[0086] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 6 As shown by Figure 6It can be seen that the diffraction pattern shows an all-silicon molecular sieve without any characteristic diffraction peak corresponding to the palladium element. The morphology of the obtained catalyst is uniform, basically hexagonal, and its crystal thickness is 23nm on average. The surface of the catalyst is smooth, without obvious granular substances. According to elemental analysis, based on 100 parts by weight of the catalyst, the metal Pd element in the catalyst is 0.90 parts by weight, which is in line with the theoretical feed. The metal Pd nanoparticles are uniformly encapsulated, with a particle size of 0.5 to 2.5nm.
[0087] Example 6
[0088] Except for the following parameters and settings, the rest are the same as Example 1: tetrapropylammonium hydroxide is replaced by tetramethylammonium hydroxide.
[0089] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 7 As shown by Figure 7 It can be seen that the diffraction pattern shows an all-silicon molecular sieve without any characteristic diffraction peak corresponding to the palladium element. The morphology of the obtained catalyst is uniform, basically hexagonal, and its crystal thickness is 23nm on average. The surface of the catalyst is smooth, without obvious granular substances. According to elemental analysis, based on 100 parts by weight of the catalyst, the metal Pd element in the catalyst is 0.90 parts by weight, which is in line with the theoretical feed. The metal Pd nanoparticles are uniformly encapsulated, with a particle size of 0.4 to 2.0nm.
[0090] Example 7
[0091] The following parameters and settings are the same as those in Example 1: tetrapropylammonium bromide is replaced with tetramethylammonium bromide.
[0092] The X-ray diffraction pattern of the catalyst prepared in this example (see Figure 7 ), the diffraction pattern shows an all-silicon molecular sieve without any characteristic diffraction peak corresponding to the palladium element. The morphology of the obtained catalyst is uniform, basically hexagonal, and the average crystal thickness is 20nm. The surface of the catalyst is smooth, without obvious granular substances. According to elemental analysis, based on 100 parts by weight of the catalyst, the metal Pd element in the catalyst is 0.87 parts by weight, which is consistent with the theoretical feed. The metal Pd nanoparticles are uniformly encapsulated, and the particle size is 0.6 to 2.1nm.
[0093] Comparative Example 1
[0094] Except for the following parameters and settings, the rest are the same as Example 1: no ammonium fluoride solution (ie, solution B) is added.
[0095] The X-ray diffraction pattern of the catalyst prepared in this comparative example (see Figure 7), the diffraction pattern shows an all-silicon molecular sieve without any characteristic diffraction peak corresponding to the palladium element. Figure 8 The morphology of the obtained catalyst is uniform, and the morphology is slightly different from that of the catalyst in Example 1. The average crystal thickness is 35nm, which is slightly thicker. The surface of the catalyst is smooth, and there is no obvious granular material. According to elemental analysis, based on 100 parts by weight of the catalyst, the metal Pd element in the catalyst is 0.88 parts by weight, which is consistent with the theoretical feed. The metal Pd nanoparticles are uniformly encapsulated, and the particle size is 0.7 to 2.6nm.
[0096] Application example - Decarbonylation of furanaldehyde to furan
[0097] The catalyst of Example 1 was used to test the catalytic decarbonylation reaction of furanaldehyde.
[0098] The specific application conditions are as follows: the test process is carried out in a fixed bed reactor, the catalyst mass is 200 mg (the mass ratio with furan carboxaldehyde is 1:5), the catalytic process conditions are: the reaction pressure is normal pressure, the molar ratio of hydrogen to furan carboxaldehyde is 80:1, the reaction temperature is 250 ° C, and the furan carboxaldehyde space velocity is 0.8 h -1 The catalytic time was 8 hours, and samples were taken and analyzed every hour.
[0099] Detection method: After the reaction, samples were collected and the product composition was analyzed by gas chromatography, and then the furan formaldehyde conversion rate and furan selectivity were calculated. The catalytic results of the catalyst in Example 1 are shown in Tables 1 and Fig. 9 . Fig. 9 The meaning is the same as that shown in Table 1. The calculation formula of furan carboxaldehyde conversion rate is: furan carboxaldehyde conversion rate = [(furan carboxaldehyde carbon mole number in feed) - (furan carboxaldehyde carbon mole number in discharge)] ÷ (furan carboxaldehyde carbon mole number in feed) × 100%.
[0100] The formula for calculating the selectivity of furan is: furan selectivity = (molar number of furan carbon in the output) ÷ (total molar number of carbon of all carbon-containing products in the output) × 100%.
[0101] Table 1
[0102]
[0103] From Table 1 and Fig. 9 It can be seen that the catalyst obtained in Example 1 has a high catalytic activity for the decarbonylation of furanaldehyde to produce furan, wherein the conversion rate of furanaldehyde can reach 100%, and the selectivity of furan is 96.2%, which has a high selectivity for furan, thereby reducing the cost of product separation and having obvious economic benefits.
[0104] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A catalyst, characterized in that Including all-silicon molecular sieves and metal nanoparticles; wherein, The particle size of the metal nanoparticles is 0.5 to 3.5 nm; the metal nanoparticles are dispersed inside the all-silicon molecular sieve; The metal element in the metal nanoparticles is selected from one or more of Pd, Pt and Rh; based on 100 parts by weight of the catalyst, the metal nanoparticles are 0.2 to 4.5 parts by weight; The catalyst has a flake structure.
2. The catalyst according to claim 1, characterized in that The metal element in the metal nanoparticles is selected from one of Pd, Pt and Rh.
3. The catalyst according to claim 1, characterized in that The catalyst has a hexagonal sheet structure.
4. A method for preparing the catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, mixing a silicon-containing raw material, alkylammonium hydroxide and water to obtain a first mixture; preliminarily crystallizing the obtained first mixture at 50-100° C. to obtain a seed suspension; the molar ratio of silicon element, alkylammonium hydroxide and water in the silicon-containing raw material is 1:0.1-0.5:6-26; Step 2, mixing a silicon-containing raw material, alkylammonium hydroxide, alkylammonium bromide, a water-soluble metal salt and water to obtain a solution A; wherein in the solution A, the molar ratio of the silicon element in the silicon-containing raw material, the alkylammonium hydroxide, the alkylammonium bromide, the metal element in the water-soluble metal salt and water is 1:0.01-0.4:0.01-0.4:0.0004-0.03:20-200; Step 3, mixing the seed suspension in step 1 and the solution A in step 2 to obtain a second mixture; wherein the molar ratio of silicon in the seed suspension to silicon in the solution A is 0.5 to 2.5:1; Step 4, mixing the ammonium fluoride-containing solution B with the second mixture to obtain a third mixture; wherein the molar ratio of ammonium fluoride to water in the ammonium fluoride-containing solution B is 1:30-300; and the molar ratio of silicon element in the second mixture to ammonium fluoride in the solution B is 1:0.05-0.8; Step 5, crystallizing the third mixture at 150-180° C., separating the solid and the liquid, and obtaining an initial solid; washing and drying the obtained initial solid to obtain a dry solid; and then reducing the dry solid in a hydrogen atmosphere at 350-450° C. to obtain the catalyst.
5. The method according to claim 4, characterized in that The silicon-containing raw material is selected from silicate or alkaline silica sol; the silicate is selected from one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl orthosilicate and butyl orthosilicate.
6. The method according to claim 4, characterized in that The alkylammonium hydroxide is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, dimethyldiethylammonium hydroxide and dimethyldipropylammonium hydroxide.
7. The method according to claim 4, characterized in that The alkylammonium bromide is selected from one or more of tetramethylammonium bromide, tetraethylammonium bromide and tetrapropylammonium bromide.
8. The method according to claim 4, characterized in that The water-soluble metal salt is a complex of a water-soluble metal salt and ethylenediamine.
9. Use of the catalyst according to any one of claims 1 to 3 in catalytic decarbonylation of furanaldehyde to prepare furan.
10. A method for preparing furan by catalytic decarbonylation of furan carboxaldehyde, characterized in that: The catalyst according to any one of claims 1 to 3 is used to catalyze the decarbonylation of furan carboxaldehyde to prepare furan, wherein the weight ratio of the catalyst to furan carboxaldehyde is 1:1 to 20.
Citation Information
Patent Citations
Catalyst for furan production by furfural liquid-phase decarbonylation, preparation method and application method thereof
CN101822982A
Palladium and platinum catalysts, their preparation, and their application in the furfural-to-furan reaction.
CN111298818B
Catalyst for preparing furan by gas-phase decarbonylation of furaldehyde
CN1308986A
Preparation method of sheet FeS-1 / Fe@S-1 with different thicknesses
CN111111743A
Method for preparing biomass-based polytetrahydrofuran from furfural
CN111234197A